Leveraging Psychological Storytelling and LinkedIn Content Strategy for Brand Awareness in the Training Industry: A Case Study of Relasi Diri - Bernardus Herdian Nugroho; Andre Noevi Rahmanto; Likha Sari Anggreni (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study aims to examine the digital content strategy on LinkedIn implemented by Relasi Diri, a personal growth and professional training company based in Indonesia. The objective is to understand how LinkedIn content contributes to building brand awareness and fostering audience engagement in the training industry. The research focuses on how storytelling, psychologically based messages, and personal branding strategies are applied to enhance the company’s positioning and credibility on a professional platform. The object of the research is the official LinkedIn page of Relasi Diri, particularly its content from January to May 2025. The study uses a qualitative case study method, collecting data through in-depth interviews with the founder, content analysis, and observation of audience interactions. Findings indicate that consistent value-based content, combined with a humanistic tone and expert narratives, effectively increases organic engagement, builds trust, and, when integrated with SEO, drives high-intent digital traffic. The use of psychological storytelling and thought leadership positions Relasi Diri not only as a service provider but also as an educational voice in the industry. In conclusion, LinkedIn can be a strategic platform for companies in the training and consulting sector to strengthen their digital presence and build long-term relationships with their audience.